2022
DOI: 10.3390/jcm11175153
|View full text |Cite
|
Sign up to set email alerts
|

Lumbosacral Transitional Vertebrae Influence on Acetabular Orientation and Pelvic Tilt

Abstract: Lumbosacral transitional vertebrae (LSTV) are common congenital variances with a prevalence found in the population up to 35.6%. The literature demonstrates an influence of LSTV on bony pelvic anatomy. The influence on the anatomical acetabular orientation, which is important for cup positioning in total hip arthroplasty, has not yet been described for patients with LSTV. A total of 53 patients with LSTV were identified from a CT Database including 819 subjects. Fifty patients with LSTV could be included and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Other parameters such as Sharp angle, CE angle, and FNSA of the hip joint did not show significant differences between the LSTV subgroups and the normal group, which is partially consistent with previous studies ( 25 , 39 ). The Sharp angle and CE angle reflect the acetabular coverage and inclination on the horizontal plane; however, LSTV mainly impacts the sagittal acetabular alignment.…”
Section: Discussionsupporting
confidence: 91%
“…Other parameters such as Sharp angle, CE angle, and FNSA of the hip joint did not show significant differences between the LSTV subgroups and the normal group, which is partially consistent with previous studies ( 25 , 39 ). The Sharp angle and CE angle reflect the acetabular coverage and inclination on the horizontal plane; however, LSTV mainly impacts the sagittal acetabular alignment.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have reported that orthopedic surgeons suggest that the appropriate cup anteversion ranges from 20–40° for the posterior approach and 5–25° for the anterolateral approach [ 14 , 15 ]. In our study, the quantified mean pelvic rotation was 2.50°.…”
Section: Discussionmentioning
confidence: 99%